Financial Shenanigans: How to Detect Accounting Gimmicks & Fraud in Financial Reports. - Merchant, Kenneth A.; Boatsman, James R. (The Accounting Review, 1994)
Abstract Reviews the book `Financial Shenanigans: How to Detect Accounting Gimmicks & Fraud in Financial Reports,' by Howard M. Schilit.